Les processus d’apprentissage et les réponses des élèves de 3e année de l’école primaire islamique de Sjarifudin dans l’apprentissage du français à travers les médias de la chanson - Sevia Octa Anjellina; Neli Purwani (Universitas Negeri Semarang, 2024)
The purpose of this research is to describe teaching and learning French with music and describe student response at SD Islam Sjarifudin. The approach used in this study is qualitative descriptive. Respondents of the research are elementary school students from SD Islam, grade 3. The primary data of this research is student responses, field notes, and documents and the secondary data is a French video song. The data collection methods used are observation, questionnaire, and documentation. After it has been collected, data is observed and its results show that learning French introduction to students in SD Islam Sjarifudin is carried out according to the RPP arranged by the teacher. During the learning process, the students are very enthusiastic and play an active role. Although, there are findings of negative responses at certain times this form of response is characteristic of learners of this level.